Validity and Reliability of Academic Grit Scale (AGS) Indonesian Version in University Students - Popie Kisdayani; Hari Setyowibowo (Psikostudia : Jurnal Psikologi, 2024)
Academic grit is important for a student. Academic grit is needed to specifically measure academic achievement. People's responses to difficulties and setbacks in their academic careers are significantly influenced by their passion, tenacity, and willpower to accomplish long-term goals in the profession. The Academic Grit Scale (AGS) is an instrument used to measure academic grit, but there are no studies that have adapted it for the population in Indonesia. Adapting and testing the Indonesian AGS psychometrics is the goal of this work. There were 442 active university students in Indonesia who took part in this study. The content validation of the measuring device is assessed using the Content Validity Index (CVI). To assess the measurement of instrument's reliability, this study used Classical Test Theory (CTT). The results showed that the mean I-CVI was .94, which means the items in the measuring instrument can measure the construct. AGS is considered reliable with a Cronbach Alpha of .884. The Confirmatory Factor Analysis (CFA) result shows that the fit model was accepted (RMSEA = .067, CFI = .962, GFI = .951, SRMR = .036, TLI = .951) which indicates that the measuring instrument can measure academic grit consistently. retain all the details. To conclude, it is found that the AGS is a valid and trustworthy tool for assessing Indonesian university students' academic grit.Grit akademik merupakan hal yang harus dimiliki bagi seorang pelajar. Grit akademik dibutuhkan untuk mengukur secara spesifik pencapaian akademik. Gairah dan ketekunan serta kegigihan individu untuk mencapai tujuan dalam jangka panjang pada bidang akademik sangat mempengaruhi bagaimana individu akan berperilaku ketika mengalami tantangan dan rintangan di perjalanan akademiknya. Academic Grit Scale (AGS) merupakan instrument yang digunakan untuk mengukur grit akademik, namun belum ada penelitian yang mengadaptasi dan menyesuaikan dengan populasi mahasiswa Indonesia. Tujuan dilakukannya penelitian ini adalah untuk mengadaptasi dan menguji psikometrik Academic Grit Scale (AGS) versi Bahasa Indonesia. Subjek pada penelitian ini adalah 442 mahasiswa aktif di Indonesia. Untuk mengevaluasi validasi konten alat ukur, digunakan Content Validity Index (CVI) dan untuk mengevaluasi reliabilitas alat ukur digunakan Classical Test Theory (CTT). Hasil penelitian menunjukkan bahwa didapatkan mean I-CVI sebesar .94 yang berarti item dalam alat ukur dapat mengukur konstruknya. AGS dianggap reliabel dengan Alpha Cronbach sebesar .884. Hasil Confirmatory Factor Analysis (CFA) menunjukkan bahwa model fit dapat diterima (RMSEA = .067, CFI = .962, GFI = .951, SRMR = .036, TLI = .951) yang menunjukkan bahwa alat ukur mampu mengukur grit akademik dengan tetap mempertahankan keseluruhan item-itemnya. Dengan hasil tersebut, disimpulkan bahwa AGS adalah skala yang cocok dan mumpuni untuk mengukur grit akademik mahasiswa Indonesia.